China in global scientific and educational area: strategies of intellectual breakthrough - Ilnytskyy, Denys; Khomenko, Olha (Skhid, 2015)
The article addresses China as a country which actively creates and effectively exploits the potential of intellectual capital in interests of social and economic development. Aim of the study is to identify key factors and strategies of a global competitive leadership of China on the basis of effective use of national innovation and intellectual potential. Ukrainian scientific and educational institutions can take advantage of potential cooperation with Chinese partners. Analysis of the objectives, programs and plans made it possible to identify the main stages of development of education, science and technology in China. Becoming conscious of negative effects of the Cultural Revolution, including the loss of higher education for social and economic development, China started reforms of national system of science and education (1-st stage - 1975 - 1994). Priorities of 2-nd stage (1995 - 2005) were deepening reforms, shaping the points of growth, sustainable funding, early integration of national innovation system into global. Securing a strong position in global scientific and educational space, increased funding, reforms for achieving global leadership and becoming innovative nation through effective implementation of intellectual capital in some sectors occurs during 3-rd stage (2006 - present). Targeted government policies to increase human capital, formation of world-class universities, along with development of IPR protection lead to increase in the number of scientific papers and patents that provide leading international position of China. In the near future China is expected to implement a strategy of transition from quantitative indicators to high quality of scientific and educational complex and improving IPR protection.